Implementation of pro- and anti-inflammatory mechanisms of sirtuin-1 in patients with chronic obstructive pulmonary disease and chronic coronary syndrome and their combination - Ya. V. Chobanu; T. O. Ilashchuk (Zaporožskij Medicinskij Žurnal)
One of the key pathogenetic aspects of chronic obstructive pulmonary disease (COPD) and chronic coronary syndrome (CCS) is endothelial dysfunction. Further study on this pathological process is relevant for a better understanding of the course and increasing the treatment effectiveness of these diseases. In this context, in recent years, there has been a growing body of evidence about sirtuins which, according to the latest research results, were capable of rebalancing vasoconstrictory and vasodilatory mediators, regulating the balance in the protease-antiprotease system, protecting endothelial cells from oxidative stress and may be useful in relation to the pathogenesis of COPD and CCS.